Is Occurrence of Harmful Algal Blooms in the Exclusive Economic Zone of India on the Rise?. (26th February 2012) - Padmakumar, K. B.; Menon, N. R.; Sanjeevan, V. N.
Abstract : Occurrence, increase in frequency, intensity and spatial coverage of harmful algal blooms during the past decade in the EEZ of India are documented here. Eighty algal blooms were recorded during the period 1998–2010. Of the eighty algal blooms, 31 blooms were formed by dinoflagellates, 27 by cyanobacteria, and 18 by diatoms. Three raphidophyte and one haptophyte blooms were also observed. Potentially toxic microalgae recorded from the Indian waters were Alexandrium spp., Gymnodinium spp. Dinophysis spp., Coolia monotis, Prorocentrum lima, and Pseudo-nitzschia spp. Examination of available data from the literature during the last hundred years and in situ observations during 1998–2010 indicates clear-cut increase in the occurrence of HABs in the Indian EEZ.